Stress and coping in patients with multiple sclerosis. A comparative study with normative sample - Lara, Sylvia; Kirchner, Teresa (Anales de Psicología / Annals of Psychology, 2012)
Multiple Sclerosis (MS), not only provokes a series of physical limitations, but also a great number of psychosocial distress. The objective of this study is twofold: 1) to establish the kind of problems commonly narrated by MS patients, the level of stress generated, the perceived degree of control and the coping strategies used to face them. 2) To compare the use of coping strategies and the degree of stress and control between MS patients and the normative sample. Method: the participants were 70 MS diagnosis patients (48 women and 22 men). The results indicate that physical disabilities, problems related to work and the lack of a sense of future projection are the main stressors that are prevalent concerns to MS patients. The strategies most frequently used by participants are Problem Solving and Positive Reappraisal and the less frequently used is Emotional Discharge. The low sense of control in these patients is related to a high intensity of stress. Furthermore, the intensity of stress is associated with a major use of avoidance strategies. No differences are found related to level of stress and sense of control between MS patients and normative sample and scarce differences related to the use of coping strategies.